2017
DOI: 10.1039/c7ra03193a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ascorbyl palmitate loaded poly(caprolactone)/silver nanoparticle embedded poly(vinyl alcohol) hybrid nanofibre mats as active wound dressings via dual-spinneret electrospinning

Abstract: AP loaded PCL/AgNP embedded PVA hybrid nanofibre mats were prepared through dual-spinneret electrospinning, which altogether contributed to wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 59 publications
0
16
0
1
Order By: Relevance
“…The wound dressings should provide a suitable moisturized environment for healing by absorbing excess exudates, and killing bacteria. Very recently, Du et al employed an electrospinning setup with two spinnerets to form PCL/polyvinyl alcohol (PVA) fibrous mats with a mixture of fibers, and loaded with AgNPs for mice wound healing [181]. Hydrolytic PVA maintains a moist wound environment to promote fibroblast adhesion, while PCL provides structural stability to impart mechanical strength to the resulting mats.…”
Section: Aliphatic Polyester Nanocompositesmentioning
confidence: 99%
“…The wound dressings should provide a suitable moisturized environment for healing by absorbing excess exudates, and killing bacteria. Very recently, Du et al employed an electrospinning setup with two spinnerets to form PCL/polyvinyl alcohol (PVA) fibrous mats with a mixture of fibers, and loaded with AgNPs for mice wound healing [181]. Hydrolytic PVA maintains a moist wound environment to promote fibroblast adhesion, while PCL provides structural stability to impart mechanical strength to the resulting mats.…”
Section: Aliphatic Polyester Nanocompositesmentioning
confidence: 99%
“…11 We also studied the effectiveness of PVA concentration and reductant dosage on the sizes of Ag NPs. 15 The PVA/Ag NP nanobres with different sizes of Ag NPs are shown in Fig. 10.…”
Section: Resultsmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA), a well-known watersoluble polymer with good biocompatibility, has been widely used in several biomedical applications, like so contact lenses, wound dressing, and tissue engineering. [14][15][16] Therefore, in view of the excellent characteristic of PVA, we prepared monodispersed Ag NPs which were embedded into the PVA nanobres.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 5 wt% SSD-loaded co-electrospun PVA/PCL showed better antibacterial and reasonable cell proliferation and differentiation. Recently, Online et al fabricated PVA merged with monodispersed Ag NPs and PCL loaded with Ascorbyl palmitate (AP) by dual-spinneret electrospinning [95]. The NIH-3T3 fibroblast cells were seeded on the scaffold mats, and it was shown that AP inhibits the toxic effects of Ag NPs on cell proliferation.…”
Section: Biomedical Applications Of Polymer-based Electrospun Nanomentioning
confidence: 99%